Effect of fluidized-bed drying method on seed vigor of two Soybean cultivars by cold test - جلال مؤمنی; مجید شکرپور; محمد صدقی; محمد انتصاری; اشکان عباسیان (علوم و فناوری بذر ایران)
In order to evaluate the effect oftemperature and bed drying methodon vigor of two cultivars ofsoybeanseeds Katoul (DPX) and Sari (JK), an experiment was performed at Agricultural Engineering Research Institute (AERI) and Seed and Plant Certification and Registration Research Institute (SPCRI) in Karaj. Seeds with primary moisture 16-17% dried at four temperatures 30˚C, 40˚C, 50˚C and 60˚C and three beds (stable,threshold fluidizingand fluidized). Then percentage of normal seedling, length of seedling, seedling dry weight,seedling vigorindex, final seedling emergenceand leaf area index were assessed. Result showed that temperature and bed affected traits. The highest germination(normal seedling) percentage wasrelated to Sari (JK) at 40°C in the fixed bed.Result showed that length and dry weight of seedling in Katoul (DPX) was  better than Sari (JK). Also higher leaf area index was observed in Katoul (DPX) at 30°Cin the threshold fluidized bed.According to the results, 30-40°C are suitable temperature for dryingseeds. Also constant bed in fluidized-bed drying was the best bed treatment.